1990
DOI: 10.1161/01.cir.81.4.1415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endothelin-1 in man.

Abstract: The effect of an intravenous infusion of human endothelin-1 on blood pressure and plasma concentrations of endothelin-1, potassium, sodium, renin, aldosterone, and atrial natriuretic factor was investigated in six healthy, sodium-loaded men. During the peptide's exogenous application (1.0, 2.5, and 5.0 ng/kg* min), its plasma concentrations rose from a basal value of 1.2+0.3 to 3.2+1.9, 9.9±7.6, and 56.5±50.3 pmol/l (p<0. medication was permitted for at least 4 weeks before the study. All subjects were fasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1
2

Year Published

1991
1991
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(94 citation statements)
references
References 16 publications
5
86
1
2
Order By: Relevance
“…Such changes in circulating ET-1 are much smaller than those that occur after anesthesia in rats, 29 and they are in any case still below the vasoconstrictor threshold both in vitro 30 and in vivo, as indicated for systemic and renal circulation in studies in humans undergoing ET-1 infusion. 18,31 We did not measure plasma ET-1 in this study, first because the above-reported evidence suggests that under our experimental conditions, significant variations in plasma ET-1 are very unlikely. In addition, plasma ET-1 may not reflect an increase in its tissue concentration due to an accentuated release of peptide on the basolateral side of endothelial cells.…”
Section: Montanari Et Al Effects Of L-name and Bq-123 In Human Kidneymentioning
confidence: 95%
“…Such changes in circulating ET-1 are much smaller than those that occur after anesthesia in rats, 29 and they are in any case still below the vasoconstrictor threshold both in vitro 30 and in vivo, as indicated for systemic and renal circulation in studies in humans undergoing ET-1 infusion. 18,31 We did not measure plasma ET-1 in this study, first because the above-reported evidence suggests that under our experimental conditions, significant variations in plasma ET-1 are very unlikely. In addition, plasma ET-1 may not reflect an increase in its tissue concentration due to an accentuated release of peptide on the basolateral side of endothelial cells.…”
Section: Montanari Et Al Effects Of L-name and Bq-123 In Human Kidneymentioning
confidence: 95%
“…Although an effect on the kidney or atrial myocytes cannot be ruled out, an average endothelin concentration of 57 pmol/l during intravenous infusions did not influence plasma renin activity or plasma aldosterone and atrial natriuretic peptide concentrations in normal subjects. 17 Thus, it appears unlikely that reduced renal perfusion43 with an increase of renin or a release of atrial natriuretic peptide44 contributed to the vasoconstrictor and vasodilator responses to endothelin, respectively.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…1,167 Endothelin acts as the natural counterpart to endothelium-derived NO, which exerts vasodilating, antithrombotic, and antiproliferative effects, and inhibits leukocyteadhesion to the vascular wall. 118 In addition to its arterial blood pressure rising effect in man, 168,169 ET-1 induces vascular and myocardial hypertrophy, [170][171][172] which are independent risk factors for cardiovascular morbidity and mortality. [173][174][175] Indeed, in patients with essential hypertension, carotid wall thickening and left ventricular mass correlate with reduced endothelium-dependent vasodilation.…”
Section: Endothelin and Endothelin Antagonists In Hypertensionmentioning
confidence: 99%